As pacientes ginecológicas e obstétricas no HUSM/SM: o que sabem da sua internação e a qualidade da informação recebida - Muradás, Raquel Rodrigues (2014)
The medical practice today requires an open and frank dialogue between the two poles of the relationship: physician and patient. This dialogue is the main form and source of information for the patient in treatment. The relationship between the doctor and no matter which level of attention requires more care, attention and ethics. In obstetrics, the medical-mother-fetus relationship is unique due to the complete physiological dependence of the fetus towards his/her mother. Moreover, both are considered patients by the obstetrician. All the above should be kept in mind to undertake seriously one of the first procedures to compose a true committed physician-patient relationship. Furthermore the patient needs always to be informed of the reasons of being hospitalized. This information should include: the most usual course of the process of health and disease, the possible diagnostic and therapeutic procedures that will be instituted in the case and the reasonable alternative procedures. It is highly important to inform the patients about their rights and queries, in a way that would strengthen their autonomy. The objective of this dissertation is to understand the perception of women wards at the University Hospital of Santa Maria (HUSM), about the quality and adequacy of information provided to them during their stay. Moreover, this study seeks to under their stand and their knowledge and believes about the process of health/disease. This study was designed as both: quantitative research and qualitative research. Therefore, the following research question was used to construct this dissertation: what is the vision/perception of patients admitted in the second floor of HUSM on the quality of information on the process of health-disease by professionals who care for them?